Assessment of health literacy in the population of chronic patients by using of FCCHL questionnaire - Šesto, Sofija; Lević, Marija; Milošević Georgiev, Andrijana; Stanojlović, Marijana; Radojković, Jovana; Radojičić, Milica; Femić, Ivana; Bogavac - Stanojević, Nataša; Krajnović, Dušanka (Archives of Pharmacy, 2022)
Health literacy (HL) is an important determinant of health, which has a significant role in the management of chronic diseases and therapy. The aim was to assess functional, communicative, critical, and total HL and evaluate differences in literacy levels. A cross-sectional study was performed on a sample in health institutions (pharmacies, health centers) in urban and rural areas during 2021/2022. A validated version of the FCCHL questionnaire was used, which assessed HL, in relation to age, gender, place of residence, chronic disease, marital status, number of children, level of education, employment, smoking and self-assessment of health. In the sample of 349 chronic patients, women (58.2%) and diabetics (71.9%) dominated. Although the majority (87.1%) showed adequate HL, there are differences among patients according to HL levels, except for gender and smoking. There is the least difference in relation to the level of functional HL, and the most difference is shown in critical HL. Chronic patients who had a higher level of education, live in Belgrade, parents and married (χ2 = 28.36, p <0.001, χ2 = 4.19, p <0.05, χ2 = 6.56, p (0.05, χ2 = 14.99, p <0.05, respectively) had statistically significant higher levels of critical HL. We concluded that the application of the FCCHL questionnaire can reveal differences in the levels of total HL and more importantly critical and communicative literacy. These results may be important to clinicians in practice to easier identify patients who need help with management and use of information for better disease control.